2014
DOI: 10.1254/jphs.14r11cp
|View full text |Cite
|
Sign up to set email alerts
|

Connection Between Periodontitis and Alzheimer’s Disease: Possible Roles of Microglia and Leptomeningeal Cells

Abstract: Abstract. Neuroinflammation, inflammation of the brain, is strongly implicated in Alzheimer's disease (AD), which can be enhanced by systemic inflammation. Therefore, the initiation and progression of AD are affected by systemic diseases such as cardiovascular disease and diabetes. This concept suggests a possible link between periodontitis and AD because periodontitis is a peripheral, chronic infection that elicits a significant systemic inflammatory response. There is now growing clinical evidence that chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 30 publications
1
66
0
2
Order By: Relevance
“…The observed associations between periodontitis and cognitive impairment appear to be biologically plausible. It has been suggested that sites of periodontal infection could be significant sources of inflammatory mediators and bacterial components, which may enter the central nervous system and cause neuronal damage . Although the evidence supporting the potential association between periodontitis and cognitive impairment is increasing, the results from previous studies are not consistent with those from several studies that did not find any significant association between periodontitis and cognitive impairment.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The observed associations between periodontitis and cognitive impairment appear to be biologically plausible. It has been suggested that sites of periodontal infection could be significant sources of inflammatory mediators and bacterial components, which may enter the central nervous system and cause neuronal damage . Although the evidence supporting the potential association between periodontitis and cognitive impairment is increasing, the results from previous studies are not consistent with those from several studies that did not find any significant association between periodontitis and cognitive impairment.…”
Section: Discussionmentioning
confidence: 91%
“…16 These inflammatory mediators and bacterial components may activate brain-resident microglia to evoke neuroinflammation, which ultimately contributes to cognitive impairment. 17 This theory is partly supported by a study that demonstrated the presence of LPS from Porphyromonas gingivalis in the 12-h postmortem brain tissue samples from Alzheimer's disease cases. 18 Second, periodontitis is reported to be associated with endothelial dysfunction, 19 which plays a role in the pathogenesis of vascular cognitive impairment.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Despite the existence of numerous narrative reviews [8,9,[13][14][15][16] , the use of subjective and non-standardized methods may have led to bias [17] . To the best of our knowledge, no previous systematic approach to this emerging topic can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Development of treatments that delay the onset of AD by five years is estimated to potentially reduce the number of AD patients by half. Recently, considerable attention has been focused on lifestyle related diseases, including diabetes [1] and periodontitis [2][3][4][5], as exacerbating factors for AD. Periodontitis is also a risk factor for diabetes, and several recent clinical studies have demonstrated that periodontal treatment using antibiotics has beneficial effects on glycemic control for patients with type 2 diabetes [6].…”
Section: Introductionmentioning
confidence: 99%